Implementasi Evaluasi Pelatihan di Badan Pengembangan Sumber Daya Manusia Provinsi Kalimantan Tengah - Ainun Ni’mah; Abdul Gofur; Rustam Effendie (Concept: Journal of Social Humanities and Education, 2025)
Improving the quality of human resources in the civil service is a major challenge in realizing effective, adaptive, and professional governance. Training civil servants is an important tool for building their competence, but its success depends heavily on the extent to which the training evaluation process is carried out systematically and continuously. This study aims to describe the implementation of training evaluation at the Human Resource Development Agency (BPSDM) of Central Kalimantan Province, focusing on the implementation mechanism, assessment indicators, and follow-up on evaluation results. The method used is descriptive qualitative research, with data collection techniques through interviews, observations, and document reviews for two months, from August to September 2025. The results show that training evaluation at the Central Kalimantan Province BPSDM is carried out in an orderly and structured manner with full reference to the guidelines of the State Administration Agency (LAN). The assessment was conducted using a Google Form-based instrument distributed to participants at the end of the training. The evaluation results were used by the quality assurance team as a basis for formulating recommendations for program improvements. This study implies that the consistent application of evaluation and measurable follow-up are crucial in enhancing the quality of civil servant training programs on an ongoing basis.